A Magnetospheric Driver of Westward Traveling Surge: Plasma‐Sheet Bubble. Issue 20 (20th October 2021) - Wei, Dong; Zhang, Fei; Yang, Jian; Wang, Wenrui; Sun, Weiqin; Cui, Jun; Angelopoulos, Vassilis
Abstract: The westward traveling surge (WTS) is one of the most significant manifestations of auroral substorms. The formation and evolution of WTS are the key to understanding the dynamics of substorm. However, the generation mechanism of WTS remains unclear. This study investigates the magnetospheric driver of WTS using numerical simulations of the Inertialized Rice Convection Model. We model a typical WTS event by specifying a low‐entropy bubble injection from the magnetotail. The simulated characteristics of the WTS are consistent with typical observed features. Simulation confirms that the bubble injection creates an intense upward Region‐1 field‐aligned current to flow into the ionosphere, which is responsible for the prominent auroral structure. Moreover, the calculated speed of westward expansion of the bubble in the magnetosphere agrees very well with the speed of the westward surge in the ionosphere. Therefore, the plasma‐sheet bubble is believed to be a possible magnetospheric source of the WTS. Plain Language Summary: The westward traveling surge (WTS) is a remarkable auroral phenomenon that appears in the high latitude ionosphere during geomagnetic substorms. Following substorm onset, the auroral arcs intensify and expand poleward. The poleward expansion of aurora then forms a bulge structure with a spatial scale of hundreds of kilometer and expands westward at a speed of ∼1 km/s. However, the magnetospheric source of the WTS is still poorly understood. In this work, using the Rice Convection Model, we simulated the WTS and proposed a bubble structure as the magnetospheric counterpart of the surge. Our simulation results show the modeled characteristics of WTS are consistent with previous findings. We also found that the bubble injection in the magnetosphere can drive one current sheet connecting to the ionosphere, which further results in the formation of WTS, and that the westward drift of this bubble leads the aurora to surge westward. Key Points: Rice Convection Model is used to simulate the formation and evolution of westward traveling surge during a substorm expansion phase Plasma‐sheet bubble injection leads to an intense upward Region‐1 FACs and thus controls the dynamics of westward traveling surge The simulation shows the auroral westward traveling surge is associated with the westward azimuthal expansion of the bubble around 10 Re